2016
DOI: 10.3791/54228
|View full text |Cite
|
Sign up to set email alerts
|

Human Primary Trophoblast Cell Culture Model to Study the Protective Effects of Melatonin Against Hypoxia/reoxygenation-induced Disruption

Abstract: This protocol describes how villous cytotrophoblast cells are isolated from placentas at term by successive enzymatic digestions, followed by density centrifugation, media gradient isolation and immunomagnetic purification. As observed in vivo, mononucleated villous cytotrophoblast cells in primary culture differentiate into multinucleated syncytiotrophoblast cells after 72 hr. Compared to normoxia (8% O2), villous cytotrophoblast cells that undergo hypoxia/reoxygenation (0.5% / 8% O2) undergo increased oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
1
18
0
1
Order By: Relevance
“…Term placentas were obtained immediately after spontaneous vaginal deliveries from uncomplicated pregnancies with informed patient consent. Villous cytotrophoblasts were isolated, based on the classic trypsin‐DNase/Percoll method and modified in our laboratory . Briefly, the placenta was manually minced, weighed, and exposed to four consecutive digestion baths containing trypsin and DNAse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Term placentas were obtained immediately after spontaneous vaginal deliveries from uncomplicated pregnancies with informed patient consent. Villous cytotrophoblasts were isolated, based on the classic trypsin‐DNase/Percoll method and modified in our laboratory . Briefly, the placenta was manually minced, weighed, and exposed to four consecutive digestion baths containing trypsin and DNAse.…”
Section: Methodsmentioning
confidence: 99%
“…The pool of pellets was added to a Percoll column and centrifuged. The layer containing 40‐50% of the density, which contained mainly trophoblasts, was collected . Following the isolation, mononuclear villous trophoblasts were purified by immunomagnetic labeling using autoMACS ™ (Myltenyi Biotec, Santa Barbara, CA, USA), as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we isolated cells from Trpv6 +/+ , Trpv6 +/-, and Trpv6 -/placentas. Staining of the trophoblast-specific marker proteins dysferlin, cytokeratin 7, and GCM1 (28,(30)(31)(32)(33) showed that >90% of the isolated cells were indeed trophoblasts ( Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Было установлено, что снижение уровня мелатонина связано с развитием преэклампсии, при этом циркулирующие уровни мелатонина, по-видимому, не подвержены сезонным изменениям во время беременности [19].…”
Section: влияние мелатонина на хроническую плацентарную недостаточностьunclassified